KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENGOPTIMALKAN KINERJA GURU DI MTS AL-RAISIYAH SEKARBELA LOMBOK BARAT - Ariyanti, Novi Ariyanti; Miranda , Yulia (UII Darullughah Waddawah Pasuruan, 2022)
The main parameters of the principal's success relate to the skills and abilities in managing all the potential and resources of the school and carrying out management functions including planning, organizing, implementing, controlling properly and optimally. With the managerial skills possessed by the principal, teachers as an educational resource have an important role in improving the quality of education. The purpose of this study was to determine the planning, implementation, and evaluation of the principal's managerial skills in optimizing teacher performance at MTs Al-Raisiyah Sekarbela West Lombok. This research uses a qualitative approach with a case study design. Data collection instruments including participation observations, structured interviews and documentation are the researchers' choice to obtain information. Miles And Huberman's version of data analysis with three activity flows, namely data reduction, presentation of conclusion drawing data. The results of this study show that the managerial competence of the principal including planning, implementing and evaluating the program is able to improve teacher performance and performance. This is evidenced by the commitment of the principal in formulating a program that refers to the protofolio of teacher certification, namely planning and implementing learning, assessment from superiors by scheduling supervision and participation in scientific forums such as MGMP. At the evaluation stage, it is in the form of direct and indirect supervision, as well as an evaluation meeting every three months.